Local history periodicals of the Russian Federation at the turn of the centuries: the ways and peculiarities of development - L. I. Novikova; E. I. Trubina (Библиосфера)
We consider the current state of domestic local history journals and anthologies, are described by their typological traits and characteristics and trends. The data on the geography and frequency of publications, information about the founders, publishers, sources of funding. Analyzes the reasons that hinder the development of local history periodicals and their possible ways of the solution.